Population Pharmacokinetic Analyses of Isoniazid in Tuberculosis Treatment: A Systematic Review - Anh Tuan, Le; Son Nhat, Bui; Hong Long, Nguyen; Thi Ngan, Nguyen; Thi Lien Huong, Nguyen; Thi Luyen, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 1DO - 10.25073/2588-1132/vnumps.4278, 2021)
This systematic review provides knowledge concerning population pharmacokinetics of isoniazid (INH) and identifies factors influencing INH pharmacokinetic variability. Pubmed and Embase databases were systematically searched from inception to July, 2017. The review includes 10 relevant articles from reference lists and all population pharmacokinetic studies of INH written in English, conducted in human (either healthy subjects or pulmonary tuberculosis patients). Most of the ten reviewed articles suggested a two-compartment model with first-order kinetics for INH with a transit-compartment model for absorption. The frequently reported significant predictor for INH clearance was of NAT2 acetylator types (slow/intermediate/fast), while weight was a significant covariate for INH volume of distribution (both central and peripheral). In children, enzyme maturation had a profound effect on INH clearance. Keywords Population pharmacokinetics, isoniazid. References [1] World Health Organization, Global Tuberculosis Report 2019. https://apps.who.int/iris/bitstream/handle/10665/329368/9789241565714-eng.pdf (accessed 18 December 2019). [2] United Nations, Transforming our world: The 2030 agenda for sustainable development, New York, USA, 2015. [3] K. Takayama, L. Wang, H.L. David, Effect of isoniazid on the in vivo mycolic acid synthesis, cell growth, and viability of Mycobacterium tuberculosis, Antimicrob Agents Chemother 2.1 (1972) 29-35. https://doi.org/10.1128/aac.2.1.29 [4] A. Jindani, V.R. Aber, E. A. Edwards, D. A. Mitchison, The early bactericidal activity of drugs in patients with pulmonary tuberculosis. Am Rev Respir Dis 121(6) (1980) 939-49. https://doi.org/10.1164/arrd.1980.121.6.939 [5] P.R. Donald, The influence of human N-acetyltransferase genotype on the early bactericidal activity of isoniazid. Clin Infect Dis 39(10) (2004) 1425-30. https://doi.org/10.1086/424999 [6] D.A. Mitchison, Basic mechanisms of chemotherapy, Chest 76(6 Suppl) (1979) 771-81. https://doi.org/10.1378/chest.76.6_supplement.771 [7] H. McIlleron et al., Determinants of rifampin, isoniazid, pyrazinamide, and ethambutol pharmacokinetics in a cohort of tuberculosis patients, Antimicrob Agents Chemother 50(4) (2006) 1170-7. https://doi.org/10.1128/aac.50.4.1170-1177.2006 [8] S. Chideya et al., Isoniazid, rifampin, ethambutol, and pyrazinamide pharmacokinetics and treatment outcomes among a predominantly HIV-infected cohort of adults with tuberculosis from Botswana, Clin Infect Dis 48(12) (2009) 1685-94. https://doi.org/10.1086/599040 [9] N. Singh et al., Study of NAT2 gene polymorphisms in an Indian population: association with plasma isoniazid concentration in a cohort of tuberculosis patients. Mol Diagn Ther 13(1) (2009) 49-58. https://doi.org/10.1007/bf03256314 [10] N. Buchanan, C. Eyberg, M.D. Davis, Isoniazid pharmacokinetics in kwashiorkor. S Afr Med J 56(8) (1979) 299-300. [11] U.S. Food and Drug Administration (1999), "Guidance for Industry. Population pharmacokinetics",Retrieved from http://www.fda.gov/downloads/Drugs/.../Guidances/UCM072137.pdf [12] D. R Mould, R. N. Upton, Basic concepts in population modeling, simulation, and model‐based drug development, CPT: pharmacometrics & systems pharmacology 1(9) (2012) 1-14. https://doi.org/10.1038/psp.2012.4 [13] P. Denti et al., Pharmacokinetics of isoniazid, pyrazinamide, and ethambutol in newly diagnosed pulmonary TB patients in Tanzania, PLoS ONE 10(10) (2015), e0141002. https://doi.org/10.1371/journal.pone.0141002 [14] B. Guiastrennec et al., Suboptimal Antituberculosis Drug Concentrations and Outcomes in Small and HIV-Coinfected Children in India: Recommendations for Dose Modifications, Clin Pharmacol Ther 104(4) (2017), 733-741. https://doi.org/10.1002/cpt.987 [15] M. Kinzig-Schippers et al., Should we use N-acetyltransferase type 2 genotyping to personalize isoniazid doses?, Antimicrobial Agents and Chemotherapy 49(5) (2005), 1733-1738. https://doi.org/10.1128/aac.49.5.1733-1738.2005 [16] J.J. Kiser et al., Isoniazid pharmacokinetics, pharmacodynamics, and dosing in South African infants, Therapeutic Drug Monitoring 34(4) (2012) 446-451. https://doi.org/10.1097/ftd.0b013e31825c4bc3 [17] L. Lalande, Population modeling and simulation study of the pharmacokinetics and antituberculosis pharmacodynamics of isoniazid in lungs, Antimicrobial Agents and Chemotherapy 59(9) (2015) 5181-5189. https://doi.org/10.1128/aac.00462-15 [18] C. Magis-Escurra et al., Population pharmacokinetics and limited sampling strategy for first-line tuberculosis drugs and moxifloxacin, International Journal of Antimicrobial Agents 44(3) (2014) 229-234. https://doi.org/10.1016/j.ijantimicag.2014.04.019 [19] C.A. Peloquin et al., Population pharmacokinetic modeling of isoniazid, rifampin, and pyrazinamide, Antimicrobial Agents and Chemotherapy 41(12) (1997) 2670-2679. https://doi.org/10.1128/aac.41.12.2670 [20] K.Y. Seng et al., Population pharmacokinetic analysis of isoniazid, acetylisoniazid, and isonicotinic acid in healthy volunteers, Antimicrobial Agents and Chemotherapy 59(11) (2015) 6791-6799. https://doi.org/10.1128/aac.01244-15 [21] J.J. Wilkins et al., Variability in the population pharmacokinetics of isoniazid in South African tuberculosis patients, British Journal of Clinical Pharmacology 72(1) (2011) 51-62. https://doi.org/10.1111/j.1365-2125.2011.03940.x [22] S.P. Zvada et al., Population pharmacokinetics of rifampicin, pyrazinamide and isoniazid in children with tuberculosis: In silico evaluation of currently recommended doses, Journal of Antimicrobial Chemotherapy 69(5) (2014) 1339-1349. https://doi.org/10.1093/jac/dkt524 [23] World Health Organization, Guidance for national tuberculosis programmes on the management of tuberculosis in children (No. WHO/HTM/TB/2014.03). World Health Organization, 2014. [24] World Health Organization, & Stop TB Initiative (World Health Organization), Treatment of tuberculosis: guidelines. World Health Organization, 2010. [25] J.S. Starke, S.M, Tuberculosis in: James D. Cherry, Ralph D. Feigin (Eds.), Textbook of Pediatric Infectious Diseases., Saunders: Philadelphia, 1998 pp. 1196-1238. [26] J.G. Pasipanodya, S. Srivastava, T. Gumbo, Meta-analysis of clinical studies supports the pharmacokinetic variability hypothesis for acquired drug resistance and failure of antituberculosis therapy, Clinical Infectious Diseases 55(2) (2012) 169-177. https://doi.org/10.1093/cid/cis353